A systematic review and meta-analysis of radiotherapy and particle beam therapy for skull base chondrosarcoma: TRP-chondrosarcoma 2024 - Nakamura, Masatoshi; Mizumoto, Masashi; Saito, Takashi; Shimizu, Shosei; Li, Yinuo; Oshiro, Yoshiko; Inaba, Masako; Hosaka, Sho; Fukushima, Hiroko; Suzuki, Ryoko; Iizumi, Takashi; Nakai, Kei; et al. (Frontiers in Oncology, 2024)
Introduction: Chondrosarcoma is a rare malignant bone tumor. Particle beam therapy (PT) can concentrate doses to targets while reducing adverse events. A meta-analysis based on a literature review was performed to examine the efficacy of PT and photon radiotherapy for skull base chondrosarcoma. Methods: The meta-analysis was conducted using 21 articles published from 1990 to 2022. Results: After PT, the 3-and 5-year overall survival (OS) rates were 94.1% (95% confidence interval [CI]: 91.0-96.2%) and 93.9% (95% CI: 90.6-96.1%), respectively, and the 3-and 5-year local control rates were 95.4% (95% CI: 92.0-97.4%) and 90.1% (95% CI: 76.8-96.0%), respectively. Metaregression analysis revealed a significant association of PT with a superior 5-year OS rate compared to three-dimensional conformal radiotherapy (p < 0.001). In the studies used in the meta-analysis, the major adverse event of grade 2 or higher was temporal lobe necrosis (incidence 1-18%, median 7%). Conclusion: PT for skull base chondrosarcoma had a good outcome and may be a valuable option among radiotherapy modalities. However, high-dose postoperative irradiation of skull base chondrosarcoma can cause adverse events such as temporal lobe necrosis.